2021
DOI: 10.1101/2021.12.20.472907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying Plant Genes Shaping Microbiota Composition in the Barley Rhizosphere

Abstract: A prerequisite to exploiting soil microbes for sustainable crop production is the identification of the plant genes shaping microbiota composition in the rhizosphere, the interface between roots and soil. Here we used metagenomics information as an external quantitative phenotype to map the host genetic determinants of the rhizosphere microbiota in wild and domesticated genotypes of barley, the fourth most cultivated cereal globally. We identified a small number of loci with a major effect on the composition o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 124 publications
3
6
0
Order By: Relevance
“…These GWAS revealed a highly polygenic architecture, suggesting a control of natural microbiota assembly by an extensive number of Quantitative Trait Loci (QTLs) with a small effect. A similar result was recently obtained with traditional linkage mapping performed in barley (Escudero-Martinez et al 2022) and tomato (Oyserman et al 2022).…”
Section: Introductionsupporting
confidence: 88%
“…These GWAS revealed a highly polygenic architecture, suggesting a control of natural microbiota assembly by an extensive number of Quantitative Trait Loci (QTLs) with a small effect. A similar result was recently obtained with traditional linkage mapping performed in barley (Escudero-Martinez et al 2022) and tomato (Oyserman et al 2022).…”
Section: Introductionsupporting
confidence: 88%
“…Consequently, and despite the limited number, these genotypes may capture the “extremes” of the evolutionary pressure on the host recruitment cues of the barley microbiota. Plants were grown under glasshouse conditions (Methods) in an agricultural soil previously used for microbiota investigations and designated ‘Quarryfield’ (31, 33, 34, 40). Pots containing the individual genotypes, and unplanted soil controls (hereafter ‘Bulk’), were supplemented with three modified Hoagland’s solution preparations (41) containing all essential macro and micronutrients and three levels of mineral nitrogen (Table S1): the optimum required for barley growth (N100%), a quarter of dosage (N25%) or no nitrogen (N0%).…”
Section: Resultsmentioning
confidence: 99%
“…As wild and domesticated barley plants display differential responses to nitrogen fertilisation (50) and a genotype-dependent control of rhizodeposition (51), the characterisation of primary and secondary metabolites released in the barley rhizosphere may provide mechanistic insights into microbiota diversification in barley. However, as recent investigations revealed that the host genetic control of the rhizosphere microbiota in wild and domesticated barley display a quantitative inheritance (32, 34), additional experiments with dedicated genetic material are required to untangle the molecular mechanisms linking nitrogen availability with microbiota diversification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations